A point of care test for the determination of amniotic fluid interleukin-6 and the chemokine CXCL-10/IP-10. (20th October 2014) - Chaemsaithong, Piya; Romero, Roberto; Korzeniewski, Steven J.; Dong, Zhong; Yeo, Lami; Hassan, Sonia S.; Kim, Yeon Mee; Yoon, Bo Hyun; Chaiworapongsa, Tinnakorn
Abstract: Objective : Intra-amniotic inflammation is a mechanism of disease implicated in preterm labor, preterm prelabor rupture of membrane, cervical insufficiency, a short cervix, and idiopathic vaginal bleeding. Determination of interleukin (IL)-6 with immunoassays has been proven for more than two decades to be an excellent method for the detection of intra-amniotic inflammation. However, assessment of IL-6 for this indication has been based on immunoassays which are not clinically available, and this has been an obstacle for the implementation of this test in clinical practice. It is now possible to obtain results within 20 min with a point of care (POC) test which requires minimal laboratory support. This test is based on lateral flow-based immunoassay. The objective of this study was to compare amniotic fluid (AF) IL-6 and interferon-γ – inducible protein 10 (IP-10 or CXCL-10) concentrations determined using lateral flow-based immunoassay or POC test and standard enzyme-linked immunosorbent assay (ELISA) techniques. Material and methods : AF samples were collected from patients with singleton gestations and symptoms of preterm labor ( n = 20). AF IL-6 and IP-10 concentrations were determined by lateral flow-based immunoassay and ELISA. Intra-amniotic inflammation was defined as AF IL-6 ≥ 2.6 ng/ml. AF IL-6 and IP-10 concentrations between two assays were compared. Results : (1) Lateral flow-based immunoassay POC AF IL-6 and IP-10 test results were strongly correlated with concentrations of this cytokine/chemokine determined by ELISA (Spearman's ρ = 0.92 and 0.83, respectively, both p < 0.0001); (2) AF IL-6 concentrations determined by the lateral flow-based immunoassay test were, on average, 30% lower than those determined by ELISA, and the median difference was statistically significant ( p < 0.0001); and (3) in contrast, AF IP-10 concentrations determined by the lateral flow-based immunoassay test were, on average, only 7% lower than those determined by ELISA, and the median difference was not statistically significant ( p = 0.81). Conclusion : AF IL-6 and IP-10 concentrations determined using a lateral flow-based immunoassay POC are strongly correlated with concentrations determined by conventional ELISA. This justifies further studies about the diagnostic indices and predictive values of this POC test.